Does Positioning During Oral and Maxillofacial Surgery Operations Influence the Development of Upper Extremity Peripheral Neuropathy? - Champion, Allen F.; Congiusta, Anthony D.; Manski, Alyssa F.; Lee, Jung-me; Duca, Aviana (Journal of oral and maxillofacial surgery, 2024)
Controversy exists regarding the role of specific etiology and mitigating factors in perioperative upper extremity peripheral neuropathy (PUN) development during oral and maxillofacial surgery (OMS) procedures. The purpose of this study was to measure the association between upper extremity (UE) positioning and developing PUN in OMS operations. The investigators implemented a retrospective cohort study. Patients referred to the Department of Oral and Maxillofacial Surgery at Jefferson Health who underwent orthognathic, telegnathic, or free flap surgery from April 2017 through December 2021 were identified. Exclusion criteria were age less than 13, revision surgery, ablative case without free flap reconstruction, incomplete medical record, pre-existing neuropathy, and UE position other than tucked or abducted. The predictor variable was UE position during surgery, which had 2 levels—tucked or abducted. The outcome variable was self-reported development of PUN, defined as new sensory and/or motor deficit in a nonoperated extremity diagnosed within 48 hours of surgery. Demographic covariates included age, gender, and race. Perioperative covariates included American Society of Anesthesiologists physical status and body mass index (BMI). The operative covariate was general anesthesia (GA) duration. Descriptive statistics were calculated. Shapiro-Wilk test was used to assess normality of the sample. Categorical variables were analyzed with Fisher's exact test. Continuous variables were analyzed with Mann-Whitney U test. Significance was defined at P < .05. Of the 432 patients identified, 342 met inclusion criteria. Median (interquartile range) ages for the abducted and tucked cohorts were 40 (31) and 34 (28) years, respectively (P < .01). Males comprised 55.4% (n = 41) and 54.1% (n = 145) of abducted and tucked groups, respectively (P = .9). PUN frequency was 6.8% (n = 5) for abducted subjects and 3.7% (n = 10) for tucked subjects (relative risk 1.8, 95% confidence interval [0.7, 5.1]; P = .33). PUN was associated with gender (P = .01), American Society of Anesthesiologists status (P = .03), BMI (P = .01), and GA duration (P < .01) on bivariate analysis. When adjusting for covariates, only GA duration (P < .01) and BMI (P = .03) were associated with PUN development. The findings suggest that PUN development during OMS procedures was not associated with UE position.